Why Not All the Powerful Abuse? The Competitive Effects of Psychological Distance and Self-Control - Caiyun Huang; Siyu Tian (Frontiers in Psychology, 2021)
Building on the social distance theory of power, this study proposed the positive and negative mechanisms of power and their impacts on abusive supervision from the competitive perspectives of psychological distance and self-control. The boundary effects of independent self-construal were also analyzed. The hypotheses of this study were tested through questionnaires and an experimental study design. The Study 1 data were collected from 422 supervisors and subordinates from five private enterprises and one state-owned enterprise in Eastern China. Study 2, on the other hand, was conducted through a scenario-based experiment in which 180 part-time master of business administration (MBA) students from a university in Eastern China participated. All data were tested using polynomial regression analysis and a bootstrapping appraisal. The results revealed that (1) the relationship between power and abusive supervision is not significant; (2) psychological distance mediates the relationship between power and abusive supervision, with high power leading to higher psychological distance, which, in turn, strengthens abusive supervision; (3) self-control mediates the relationship between power and abusive supervision, with high power leading to higher self-control, which, in turn, weakens abusive supervision; (4) the mediating effect of psychological distance is stronger, and the mediating effect of self-control is weaker when independent self-construal is high rather than low. At the end of this study, the theoretical and practical implications are discussed.